Role of Homoeopathy in Respiratory Disorders – A Retrospective Study (Advancements in Homeopathic Research, 2023)
Respiratory tract infection is the most common  infection worldwide in recent years which affect  children frequently. This is mainly classified into upper  respiratory tract infection and lower respiratory tract  infection. Recurrent upper respiratory tract infection  means defined as six or more than six serious attacks  of symptoms of respiratory tract for minimum 1 year  which will affect normal functioning. Asthma is a  common public health problem around worldwide  developed countries. About 300 million people have  been affected globally due to bronchial asthma.  Homoeopathy is a system which treats patients  with individual symptoms by various methods of  homoeopathic prescription to attain an exact cure.
Keywords: Respiratory tract infection; Asthma; Pertussis; Homoeopathy